Rethinking Algorithmic Populism: Toward an Affective Algorithmic Populism Framework in Indonesian Digital Politics - Annisa Fadillah (Dinasti Research, 2026)
Ico Maly (2018, 2020) introduced the concept of algorithmic populism as a framework for understanding how populist claims are constructed through the operation of algorithms within digital platforms. However, most empirical studies underlying this concept originate from Western Europe and Latin America, where digital populism tends to be rage-driven, built on anger, confrontation, and narratives of hatred. In this regard, this article argues that this characterization is inadequate to explain the dynamics of digital populism in Indonesia, where affective mechanisms are based on humor, personal closeness, and relaxed, open performances. Empirically, this argument is anchored in the 2024 Indonesian presidential election, the country's first TikTok election, and specifically in Prabowo Subianto's Gemoy (roughly, cute or endearing) campaign, in which a previously confrontational strongman was rebranded through humor, warmth, and playful dance content that came to dominate engagement on the platform.Using a conceptual analysis approach using the theory adaptation strategy (Jaakkola, 2020) supported by a semi-systematic literature review (Snyder, 2019; Paul & Criado, 2020) with a transparent search protocol in four scientific databases (Scopus, Web of Science, Google Scholar, and SINTA) for the period 2014–2026, this article identifies three limitations of the existing framework: geographic bias, the assumption that negative emotions (anger) fuel algorithms, and the lack of cultural context. Therefore, this article proposes the development of a concept called Affective Algorithmic Populism. This development encompasses three dimensions that distinguish it from Western variants: positive affectivity, an open performative mode, and a cultural grammar in the form of an inclusive affective community. Finally, in the closing section, this article offers a research agenda for the development of algorithmic populism studies in the Global South.